Non-linear analysis of hydro-mechanical interactions in control devices during transient period: Bond graph approach. (September 2019) - Zanj, A.; He, F.
In this paper, a feasibility study on modeling the multi-physical dynamic behaviors of the start period of hydro-mechanical control devices is presented. Using a novel multi-model Bond graph approach, a nonlinear, variable degree-of-freedom, state-space model is developed for a typical pressure regulator during its start period. Simulation studies demonstrate the essential physical behavior of the regulator during the transient period, and confirm the integrity of the resulting nonlinear model of the system.